Growth Performance and Initial Heritability Estimates for Growth Traits in Juvenile Sea Urchin Tripneustes gratilla - Pante, Ma. Josefa; dela Cruz, Talna Lorena; Garvida, Joy Joseph (Science Diliman: A Journal of Pure and Applied Sciences; Vol 19 No 1 (2007), 2007)
Genetic improvement of performance traits of maricultured species is becoming an important concern. Improvement of performance traits is important for two reasons: it enhances the growth and survival of the animals and it translates to economic gains to the fish farmer. In the sea urchin, Tripneustes gratilla, growth performance of the different families and heritabilities for wet weight, test diameter and test height were estimated from 1,020 offspring from a mating of each of the 15 males with 1 or 2 females. Measurements were done monthly starting at the grow-out stage or four months after hatching. There were significant family differences for the performance traits in sea urchin reared in tanks at the BML hatchery as revealed by ANOVA. Estimates of heritabilities based on the sire component of variance were low for wet weight (0.027), test diameter (0.033) and zero for test height. Heritabilities estimated from the dam component of variance were low for wet weight (0.063), moderate for test diameter (0.286) and test height (0.227). The results indicate that test diameter and wet weight have lowly heritable traits, which means that mass or individual selection may not be the best method for improving the traits for sea urchin populations in Bolinao. Other methods such as family and combined family selection should be explored.